Induction motors performance under symmetrical voltage sags and interruption - Test result - Surya Hardi, Amrin (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Proceeding of The 7th International Power Engineering and Optimization Conference 2013 (PEOCO 2013) at Langkawi, Malaysia on 3 June 2013 through 4 June 2013